Pelatihan Penggunaan KIT untuk Meningkatkan Kemampuan Membimbing pada Praktikum Fisika Dasar bagi Mahasiswa Program Studi Pendidikan Fisika STKIP Weetebula - Desak Made Anggraeni; Yohanis Umbu Kaleka; Etheldreda Rosari Garung (Pascasarjana Universitas Mataram, 2021)
This community service activity aims to provide training on the use of KIT for prospective co.Ass students to improve guiding skills in basic physics practicum activities. The methods used are (1) the provision of materials, (2) the implementation of devotional activities, (3) monitoring and evaluation of activities. The service was conducted in the laboratory of IPA STKIP Weetebula for 6 (six) days in April 2021 involving 3 lecturers assisted by 9 students and 20 participants. The participants were very enthusiastic to participate in this activity because most are not yet proficient in using practicum tools. this activity can add insight and skills of students in using KIT IPA in IPA Laboratory STKIP Weetebula